PENINGKATAN HASIL BELAJAR KPK DAN FPB DENGAN PENDEKATAN PENDIDIKAN REALISTIK INDONESIA DI SEKOLAH DASAR - Aulia, Ruzi Patika; Ahmad, Syafri; Zen, Mulyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract            The purpose of the research was to improve the student’s learning achievement on the Lowest Common Multiple and The Highes Common Factor Topics in Elementary School by using PMRI approach. The subject of the research was the teacher and the student in grade IV of SDN 07 Balingka Kecamatan IV Koto. From cycle I to cycle II, the score of the lesson plan increased from 80,36% (very good) to 89,28% (very good), the teacher’s activities improved from 77,5% (good) to 90% (very good), and the student’s learning achievement on cognitive aspect increased from 46,5% (low) to 89% (very good). Based on these result, it was concluded that the use of PMRI approach could increase the students learning achievement on the Lowest Common Multiple and The Highes Common Factor Topics in Elementary School. Key terms: Learning Achievement on the Lowest Common Multiple and the Highes Common Factor Topics, PMRI apporoach